2017
DOI: 10.1038/ncomms14944
|View full text |Cite|
|
Sign up to set email alerts
|

Phylogenetic analysis of metastatic progression in breast cancer using somatic mutations and copy number aberrations

Abstract: Several studies using genome-wide molecular techniques have reported various degrees of genetic heterogeneity between primary tumours and their distant metastases. However, it has been difficult to discern patterns of dissemination owing to the limited number of patients and available metastases. Here, we use phylogenetic techniques on data generated using whole-exome sequencing and copy number profiling of primary and multiple-matched metastatic tumours from ten autopsied patients to infer the evolutionary hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
138
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 55 publications
13
138
1
Order By: Relevance
“…Large-scale analyses of data sets with multiple metastases per patient may establish genetic profiles most commonly associated with cancers disseminated from single versus multiple subclones, possibly enabling determination of the tumor evolution pattern (and thus the most effective treatment protocol) in a newly diagnosed patient without the benefit of genetic information from multiple metastases. During the preparation of this manuscript, Brown et al reported similar results using primary and metastatic lesions from 10 autopsy patients (24). Their results and conclusions are strikingly similar to our own data, lending further credence to the idea that evolutionary patterns of metastases can be quite variable and may depend on the genetic complexity of the patient's primary tumor.…”
Section: Discussionsupporting
confidence: 75%
“…Large-scale analyses of data sets with multiple metastases per patient may establish genetic profiles most commonly associated with cancers disseminated from single versus multiple subclones, possibly enabling determination of the tumor evolution pattern (and thus the most effective treatment protocol) in a newly diagnosed patient without the benefit of genetic information from multiple metastases. During the preparation of this manuscript, Brown et al reported similar results using primary and metastatic lesions from 10 autopsy patients (24). Their results and conclusions are strikingly similar to our own data, lending further credence to the idea that evolutionary patterns of metastases can be quite variable and may depend on the genetic complexity of the patient's primary tumor.…”
Section: Discussionsupporting
confidence: 75%
“…Multiple efforts to understand the genetic evolution of metastasis by sequencing matched primary tumors and metastases via a single matched pair, or single-cell sequencing, revealed both linear expansion of a single clone from the primary tumor to a metastasis (17)(18)(19)(20)(21), branched evolution of metastasis (22,23), and cross-seeding of metastases (24). Few of these studies, however, span multiple subtypes of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer progression, however, is a very fast and aggressive form of evolution with limited data supporting neutral evolution [5], but rather there is evidence of selection [2,5] -something that is particularly true in tumour samples after a relapse [18,10,5], where the tumour has already been highly selected by the therapy targeted to destroy it. Thus, one would be expect that we must abandon the strict Infinite Sites Assumption in this setting, and indeed this is the case, as more and more recent studies are demonstrating that the ISA does not always hold [17,4,2]. In [4], the authors find that large deletions on several branches of a tree can span a shared locus, and thus a given mutation may be deleted independently multiple times.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, one would be expect that we must abandon the strict Infinite Sites Assumption in this setting, and indeed this is the case, as more and more recent studies are demonstrating that the ISA does not always hold [17,4,2]. In [4], the authors find that large deletions on several branches of a tree can span a shared locus, and thus a given mutation may be deleted independently multiple times. In [2], the authors show that in certain cases, homozygous deletions in cancer genomes can even provide a selective growth advantage.…”
Section: Introductionmentioning
confidence: 98%